ANALYSIS OF MEAT DEMAND IN MALAYSIA: MODEL CHOICE BETWEEN ROTTERDAM AND AIDS - Maria Divina S. Paraguas et al. (Proceedings of ICMSA, 2005)
Aggregated time series data for differentiated meat products namely,beef, pork, poultry and mutton were used to estimate and analyzeMalaysian market demand for meats. The study aimed to select themost appropriate demand model between the equally popularRotterdam model and tlre first difference Linear Approximate AlmostIdeal Demand System (LAIAIDS) model by using a non-nested test-Both models were accepted, but further diagnostic tests revealed thatthe first difference LA/AIDS represents more appropriately theMalaysian market demand for meat than the Rotterdam model. Also,the elasticities from the first difference LAIAIDS were found to bemore reliable than the Rotterdam model.Keywords: Non-nested tost, Rotterdam, AIDS, meat demand,Malaysia